Kajian Diminishing Return Penggunaan Faktor-Faktor Produksi Pada Usahatani Kentang di Kawasan Dieng - Pandu Farchan Jannata; Samsul Ma'rif (Teknik PWK (Perencanaan Wilayah Kota), 2017)
this research to identify which areas in the Dieng Region that has occur diminsihing return. There are three step to get the result, 1. Analyzing diminishing return; 2. Analyzing efficiency of potatoes farming;  3. Zoning of diminishing return area. This research uses a quantitative menthod, through cobb-douglas function, economy efficiency analysis and GIS. Collecting data this study used a questionnaire with the research subjects were farmers and research object is input or production factor potato farming. The results of this study found that many villages has occur diminishing return caused by the use of these inputs. In the analysis of diminishing return is known that the marginal product of input is smaller than the average product and its production elasticity negative. The villages are experiencing diminishing return due to input land area is the village of Tieng, Sembungan, Dieng, Patakbanteng, Sikunang, and Campursari. The employment affects all villages in Region Dieng in the diminishng return. While it's only village Patakbanteng and Parikesit affected by seed input. Fertilizer inputs affects all the villages in the occurrence of diminishing return. Meanwhile, the use of pesticides also affect all villages, except Sikunang village.